2019
DOI: 10.1016/j.molp.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bird Feeding Behavior by Tannin1 through Modulating the Biosynthesis of Polyphenols and Fatty Acid-Derived Volatiles in Sorghum

Abstract: Bird predation during seed maturation causes great loss to agricultural production. In this study, through GWAS analysis of a large-scale sorghum germplasm diversity panel, we identified that Tannin1, which encodes a WD40 protein functioning in the WD40/MYB/bHLH complex, controls bird feeding behavior in sorghum. Metabolic profiling analysis showed that a group of sorghum accessions preferred by birds contain mutated tan1-a/b alleles and accumulate significantly lower levels of anthocyanins and condensed tanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 53 publications
0
39
0
2
Order By: Relevance
“…This hypothesis is supported by current work on sorghum grain and its management. Xie et al (2019) studied sorghum varieties and preference by birds for feeding. They found that varieties avoided by birds had higher anthocyanin and tannin precursors (flavan-3-ols) than those that they preferred to eat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by current work on sorghum grain and its management. Xie et al (2019) studied sorghum varieties and preference by birds for feeding. They found that varieties avoided by birds had higher anthocyanin and tannin precursors (flavan-3-ols) than those that they preferred to eat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to determining the difference in polyphenols, the bird-preferred sorghum was found to have increased volatiles associated with fatty acids, as well as higher concentrations of fatty acids, including linolenic acid. Xie et al (2019) concluded that the modulation of the Tannin1 gene affects SbGL2 which is involved in transcription of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the top F ST outlier SNP (S5_3030678; F ST = 0.45) with a signature of diversifying selection, was located at ∼24.42 kb from Sobic.005G033801 , a candidate gene which encodes flavonol 3-O-glucosyltransferase protein known to be involved in anthocyanin biosynthesis pathway ( Holton and Cornish 1995 ). Anthocyanin accumulation appeared to be associated with grain pericarp color ( Awika et al 2004 , 2005 ), and protection against bird predation ( Xie et al 2019 ) in sorghum. However, the presence of pericarp color is undesirable in sorghum grains for making injera (a traditional pancake like bread in Ethiopia) for human consumption ( Ayana and Bekele 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…tan1-a has a 1 bp deletion in an exon and tan1-b has a 10 bp insertion in exon that results in frame shift (Wu et al 2012). Further research shows that WD40 can form a complex with MYB and bHLH, and promote the expression of GL2, a key negative regulator of fatty acid biosynthesis, thus reducing the level of volatile organic compounds and then resisting the birds attack (Xie et al 2019). By analysing the natural variation in grain quality in a diversity panel of 196 sorghums, 14, 14, and 492 genetic loci were found to be associated with tannins, starch and amino acids in sorghum, respectively (Kimani et al 2020).…”
Section: Grain Qualitymentioning
confidence: 99%